2013
DOI: 10.1016/j.jvs.2012.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic vein harvest for infrainguinal arterial bypass

Abstract: Endoscopic and open harvest techniques for infrainguinal arterial bypass provide similar rates of wound complications and bypass patency, whereas hemodialysis negatively affects patency after both harvest methods. Endoscopic harvest is associated with the need for less perioperative narcotics, suggesting a potential benefit of endoscopic harvest that deserves further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
2
11
0
1
Order By: Relevance
“…We showed that patency and reintervention rates were similar between the two groups, and this held out in subgroup analysis as well, when nonreversed and reversed conduits were compared and found to have comparable patency rates. In this respect, our findings are similar to reports by Wartman et al 19 and Gazoni et al,32 who showed similar patency between the two techniques. In our study, 36% of EVH patients underwent femoral endarterectomy, indicating proximal disease that was simultaneously treated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We showed that patency and reintervention rates were similar between the two groups, and this held out in subgroup analysis as well, when nonreversed and reversed conduits were compared and found to have comparable patency rates. In this respect, our findings are similar to reports by Wartman et al 19 and Gazoni et al,32 who showed similar patency between the two techniques. In our study, 36% of EVH patients underwent femoral endarterectomy, indicating proximal disease that was simultaneously treated.…”
Section: Discussionsupporting
confidence: 93%
“…Although our overall wound complication rate of 43% in the OVH group seems high, it includes all complications including Szilagyi I, and it is not too dissimilar from the previous reported rates in series from single academic centers (23%-44%). 10,11,15,19 Our study also found that both BMI and prior surgery were independently associated with wound complications. The relationship between increased BMI and surgical wound complications has been demonstrated in several previous studies.…”
Section: Discussionsupporting
confidence: 71%
“…31 One presentation abstract 32 was also excluded as the results were further published as a research paper. 33 There were no randomised control studies, and 12/18 were single-centre comparative (cohort) studies. 19e21,33e41 Only one of these was a prospective design.…”
Section: Resultsmentioning
confidence: 99%
“…23 However, another large retrospective study demonstrated that endoscopic vein harvesting was associated with decreased long-term mortality (AHR, 0.74; 95% CI, 0.60-0.92; P ¼ .007). 24 The cardiac literature has also demonstrated in a randomized controlled trial that endoscopic harvesting is 7 The use of the minimally invasive strategy for vein harvesting was also not associated with improved wound outcomes according to a recent meta-analysis. 26 The findings of this present study are consistent with the results of the meta-analysis as well as our singleinstitution study.…”
Section: Discussionmentioning
confidence: 99%
“…26 In studies in which the primary patency beyond 1 year is reported, several have demonstrated a significantly higher rate of delayed patency loss for the grafts harvested endoscopically. [13][14][15][16] In two of three studies that we identified reporting comparable delayed primary patency rates for open and endoscopic harvest techniques, 5,7,12 all the endoscopic harvesting procedures were performed by a single surgeon. 5,7 A fundamental component for the successful application of this technology is the commitment and experience of the operator performing the endoscopic vein harvesting.…”
Section: Discussionmentioning
confidence: 99%